2009
DOI: 10.1590/s1807-59322009000200007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Intra-Abdominal Pressure and Positive-End Expiratory Pressure

Abstract: OBJECTIVE: The aim of this study was to quantify the interaction between increased intra-abdominal pressure and Positive-End Expiratory Pressure. METHODS: In 30 mechanically ventilated ICU patients with a fixed tidal volume, respiratory system plateau and abdominal pressure were measured at a Positive-End Expiratory Pressure level of zero and 10 cm H 2 O. The measurements were repeated after placing a 5 kg weight on the patients’ belly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
(50 reference statements)
1
22
0
1
Order By: Relevance
“…As PEEP might influence the plateau pressure, 26 we excluded plateau pressure as a covariate from our primary logistic regression model to eliminate collinearity. We found that the association between application of high PEEP and a decreased risk of post-operative respiratory complications remained significant (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…As PEEP might influence the plateau pressure, 26 we excluded plateau pressure as a covariate from our primary logistic regression model to eliminate collinearity. We found that the association between application of high PEEP and a decreased risk of post-operative respiratory complications remained significant (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The lung, thoracic cage, and the abdominal cavity comprise a closed system with the diaphragm as the connecting interface. When there is an increase in the abdominal and diaphragmatic pressure, the pleural pressure may be altered and a decrease in total lung capacity, pulmonary compliance, and pulmonary volume may follow [33]. Frezza et al demonstrated that increases in BMI are associated with increases in intra-abdominal pressure [34].…”
Section: Discussionmentioning
confidence: 99%
“…PEEP levels >10 cm H 2 O may increase the risk of mortality and morbidity in critically ill patients with a significant increase in the intra-abdominal pressure. [33] High levels of PEEP may be necessary to maintain or restore oxygenation, despite the fact that "aggressive" mechanical ventilation can markedly affect cardiac function in a complex and often unpredictable fashion. [34] As the heart rate usually doesn't change with PEEP, the entire fall in the cardiac output is a consequence of a reduction in left ventricular stroke volume.…”
Section: Discussionmentioning
confidence: 99%